Casting of a superhydrophobic membrane composed of polysulfone/Cera flava for improved desalination using a membrane distillation process - Ray, Saikat Sinha (The Royal Society of Chemistry, 2023)
Superhydrophobic membranes are necessary for effective membrane-based seawater desalination. This paper presents the successful fabrication of a novel electrospun nanofibrous membrane composed of polysulfone and Cera flava{,} which represents a novel class of enhanced performance membranes consisting of a superhydrophobic nanofibrous layer and hydrophobic polypropylene (PP). Cera flava{,} which helps lower the surface energy{,} was found to be the ideal additive for increasing the hydrophobicity of the polysulfone (PSF) polymeric solution because of its components such as long-chain hydrocarbons{,} free acids{,} esters{,} and internal chain methylene carbons. In the fabricated membrane{,} consisting of 10 v/v% Cera flava{,} the top PSF–CF nanofibrous layer is active and the lower PP layer is supportive. The hybrid membrane possesses superhydrophobicity{,} with an average contact angle of approximately 162°{,} and showed high performance in terms of rejection and water flux. This work also examined the surface area{,} pore size distribution{,} fiber diameter{,} surface roughness{,} mechanical strength{,} water flux{,} and rejection percentage of the membrane. The salt rejection was above 99.8%{,} and a high permeate flux of approximately 6.4 LMH was maintained for 16 h of operation.